Atmospheric aerosol distribution in the Belarus-Ukraine region by the GEOS–Chem model and AERONET measurements. Issue 14 (17th July 2016) - Miatselskaya, N.; Kabashnikov, V.; Milinevsky, G.; Chaikovsky, A.; Danylevsky, V.; Bovchaliuk, V.
ABSTRACT: We use a global chemical transport model, GEOS–Chem (Goddard Earth Observing System – Chemistry model), to simulate the spatial and temporal distribution of atmospheric concentrations of specific aerosol types over the Belarus-Ukraine region for period 2010–2013. Results of the model simulation are evaluated with observations from Aerosol Robotic Network (AERONET) sites. To provide accurate comparison, we convert simulated aerosol components concentration into coarse, fine, and total aerosol column volume concentrations taking into account the hygroscopic growth of particles. Model-predicted and remotely sensed aerosol volume concentrations are in reasonable agreement. Comparison of the GEOS–Chem model results to the spatial distribution of the aerosol sources of coarse- and fine-mode fractions for the region investigated shows correspondence in general for coarse mode but differences for fine mode.